Interpreting the landscape: an interdisciplinary task (2009)
The landscape concept has been used by several disciplines and has been given multiple connotations, hence there are few agreements on its meaning. This paper is a conceptual review of the landscape, made from an integration of elements taken from different geographic disciplines, like environmental history and landscape ecology. From this interdisciplinary approach, a historical assessment is performed to cover from the origin of the term to its most recent transformation. The main purpose is to develop new theoretical tools to allow a better understanding of the role of human presence as an inseparable element of the environment when configuring ecosystems’ structure and functioning, especially those of forests that endure urban pressure.